Does financial inclusion predict a lower risk of loneliness in later life? Evidence from the AgeHeaPsyWel-HeaSeeB study 2016–2017. (3rd July 2021) - Gyasi, Razak M.; Adam, Anokye M.
Abstract: Objective: For many older people, loneliness represents a common source of impaired quality of life particularly in the context of poor access to financial services. This article examines the association between financial inclusion and loneliness in older adults and explores the moderating effects of gender and physical activity in this association. Methods: One thousand two-hundred participants completed the Short Form Revised UCLA Loneliness Scale assessing loneliness during 2016–2017 Aging, Health, Psychological Well-being and Health-seeking Behavior (AgeHeaPsyWel-HeaSeeB) Study. Financial inclusion was assessed using an 8-item Financial Instrument Scale. Results: Multiple ordinary least squares (OLS) regressions showed that increases in financial inclusion were associated with decreases in loneliness in the total sample ( β = −0.679, p < 0.001) and in women ( β = −0.787, p < 0.001) but not in men ( β = −0.594, p = 0.084). The negative effect of financial inclusion on loneliness was pronounced among those who engaged in physical activity ( β = −0.646, p < 0.042). Conclusions: Findings underscore the importance of financial inclusion for loneliness in later life particularly among older women and those who engage in physical activity. Encouraging and strengthening financial inclusion may crucially improve psychological health and emotional well-being among aging adults.